Keanekaragaman Jenis Vegetasi di Bukit Cogong Kabupaten Musi Rawas - Destien Atmi Arisandy; Merti Triyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the diversity of vegetation types in Bukit Cogong, Musi Rawas Regency based on composition, density of vegetation types. The population in this study were all plant species that exist in the Bukit Cogong vegetation of Musi Rawas Regency. This research is a qualitative descriptive study with the method used is the distance method (Point Centered Quarter), which measures the diameter of the type of vegetation of trees and shrubs closest to the sampling point. As for herbaceous vegetation using the distance method (point intercept), which is analyzing the type of herbaceous vegetation that is the fastest with the help of a point frequency frame tool. The procedure of this study refers to the area of ​​Bukit Cogong, Musi Rawas Regency, to determine the area of ​​the study area. The analysis used is density, frequency, dominance, important value index, and Shannon's diversity index and canopy stratification. The results obtained for tree level vegetation are 30 species, for bush vegetation found 16 species and for herbaceous vegetation found 17 species. The tree level diversity index in all study areas is in abundance. Conclusions, the bush level diversity index in the study areas A and B was moderate, while in the study area C the category was relatively abundant. Herbaceous diversity index is being abundant in all study areas. Keywords: Cogong Hill, Vegetation Type, Diversity